Persepsi Mahasiswa Terhadap Proses Pembelajaran Berbasis Aplikasi Learning Management System (LMS) Di Program Studi Pendidikan Biologi Universitas Muhammadiyah Luwuk - Sondeng, Mira; Kenta, Abd. Muin; Haruna, Moh. Fahri (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2023)
The learning process that uses the Moodle type Learning Management System (LMS) application in learning from the student's perspective on learning innovation, the point of view or individual assessment of something can be called perception. This study aims to determine student perceptions of the learning process based on the LMS application in the Biology Education Study Programme. This research is a descriptive qualitative research. The population of this study were active students in the Biology Education Study Programme in the 2022/2023 academic year with a sample size of 41 students. The sampling technique was carried out using saturated samples. The data collection technique used a questionnaire. Data were analysed using descriptive statistical analysis techniques. The results of this study indicate that overall student perceptions of the Learning Management System (LMS) application-based learning process in the Biology Education Study Programme at Muhammadiyah Luwuk University are in the good category